IDENTIFIKASI PENYEBAB POTENSIAL KECACATAN PRODUK DAN DAMPAKNYA DENGAN MENGGUNAKAN PENDEKATAN FAILURE MODE EFFECT ANALYSIS (FMEA) - Franka Hendra; Riki Effendi (University of Muhammadiyah Jakarta, 2018)
The main purpose of this paper is to analyze and identify failures for minimize the risk of product defects in the production process faucet part S11037S and detect the main facto of the cause of disability that occurred. The method used with Seven Plus One Type of Waste approach and the concept of Failure Mode Effect Analysis (FMEA). Results obtained from 28 types of disability on the faucet prakuk there are 5 types of frequencies that occur high frequency that is; Gomi, Hike, Kizu, Nami and Su. From the five types of defects can be identified several causes that often occur, among the causes that there are high RPN (Risk Priority Number) that is; 1. Gomi, the dominant cause is due to operator negligence at the time of production with the value of RPN = 60, 2. Hike, with the highest cause is the entry of dirt at the time of Plotting with RPN = 24, 3. Kizu, the main cause is also from operator negligence with RPN = 36 and Nami, the cause of the duplication is that the material used has a low quality. While Su factro cause has a low RPN that is 4 to 6.